2019
DOI: 10.1016/j.jebo.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Prospect theory in a dynamic game: Theory and evidence from online pay-per-bid auctions

Abstract: Abundant evidence exists that expected utility theory does not adequately describe decision making under risk. Although prospect theory is a popular alternative, it is rarely applied in strategic situations in which risk arises through individual interactions. This study fills this research gap by incorporating prospect theory preferences into a dynamic game theoretic model. Using a large field data set from multiple online pay-per-bid auction sites, the authors empirically show that their proposed model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The first order stochastic dominance constraint D(x) ⪰ (1) D( x) can thus be represented by the |V| constraints in (7) which are of type (3) with Ξ = 1 − v≤ v pv( x), ξv = 1 for every v ∈ V, and v = v + 1.…”
Section: First Order Stochastic Dominance Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first order stochastic dominance constraint D(x) ⪰ (1) D( x) can thus be represented by the |V| constraints in (7) which are of type (3) with Ξ = 1 − v≤ v pv( x), ξv = 1 for every v ∈ V, and v = v + 1.…”
Section: First Order Stochastic Dominance Constraintsmentioning
confidence: 99%
“…Where π(•) and V (•) are perturbation functions with specific properties that model how players perceive both payoffs and the likelihood of occurrence. Prospect theory has contributed in economics [32], politics [23], online auctions [7], and security [37] applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the subjectivity of players causes the differences between expected and real actions. The prospect theory is an effective descriptive theory for the behavior of players and also adequately describes situations in which players face exogenous risk (Brunner et al, 2019;Vahid-Pakdel et al, 2019). This study fills this research gap by incorporating the prospect theory into a dynamic game model with heterogeneous participants.…”
Section: Analysis Of Heterogeneous Game Playersmentioning
confidence: 99%
“…It can be concluded that human judgments have individual preferences. Prospect theory has established a successful model to simulate the psychological and behavioral characteristics of human beings, which has been widely applied in the field of engineering [27][28][29], economics [30][31][32], computer science [33][34][35], and so on. This provides a convincing explanation of the fact that the results of subjective empowerment do not conform to reality.…”
Section: Related Workmentioning
confidence: 99%